Effect of mesenchymal stem cells transplantation on heart function after acute myocardial infarction - Yang, Guo-xun (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2007)
OBJECTIVE: To investigate whether mesenchymal stem cells (MSCs) transplantation after acute myocardial infarction (AMI) can improve heart function and decrease infarct size in rabbits and their correlation